The Spacecraft Wake: Interference With Electric Field Observations and a Possibility to Detect Cold Ions. Issue 9 (31st August 2021) - André, Mats; Eriksson, Anders I.; Khotyaintsev, Yuri V.; Toledo‐Redondo, Sergio
Abstract: Wakes behind spacecraft caused by supersonic drifting positive ions are common in plasmas and disturb in situ measurements. We review the impact of wakes on observations by the Electric Field and Wave double‐probe instruments on the Cluster satellites. In the solar wind, the equivalent spacecraft charging is small compared to the ion drift energy and the wake effects are caused by the spacecraft body and can be compensated for. We present statistics of the direction, width, and electrostatic potential of wakes, and we compare with an analytical model. In the low‐density magnetospheric lobes, the equivalent positive spacecraft charging is large compared to the ion drift energy and an enhanced wake forms. In this case observations of the geophysical electric field with the double‐probe technique becomes extremely challenging. Rather, the wake can be used to estimate the flux of cold (eV) positive ions. For an intermediate range of parameters, when the equivalent charging of the spacecraft is similar to the drift energy of the ions, also the charged wire booms of a double‐probe instrument must be taken into account. We discuss an example of these effects from the MMS spacecraft near the magnetopause. We find that many observed wake characteristics provide information that can be used for scientific studies. An important example is the enhanced wakes used to estimate the outflow of ionospheric origin in the magnetospheric lobes to about 10 26 cold (eV) ions/s, constituting a large fraction of the mass outflow from planet Earth. Plain Language Summary: Wakes caused by spacecraft motion or drifting plasma are common behind spacecraft with scientific instruments and disturb in situ observations of space plasmas. We review the impact of wakes on observations by the Electric Field and Wave double‐probe instruments on the Cluster satellites. In the solar wind, the wake behind a Cluster spacecraft is caused by the spacecraft body, is narrow, and can partly be compensated for when analyzing data. In the regions above the Earth's polar regions, the wake behind a Cluster spacecraft is caused by an electrostatic structure around the positively charged spacecraft, causing an enhanced wake. The charging stops positive ions from reaching the spacecraft. Rather, this wake can be used to estimate the flux of cold (eV) positive ions escaping from the ionosphere. Above the poles the flux is about 10 26 ions/s, constituting a large fraction of the mass outflow from planet Earth. For an intermediate range of parameters, when the drift energy of the ions is comparable to the equivalent charge of the spacecraft, also the charged wire booms of a double‐probe instrument must be taken into account. We discuss an example from the MMS spacecraft near the magnetopause. Key Points: Plasma wakes are common behind scientific spacecraft Wakes in the solar wind can be compensated for in data analysis Enhanced wakes in the polar lobes can be used to detect cold outflowing ions